1980
DOI: 10.1577/1548-8659(1980)109<229:eoepac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental pH and Calcium on Ammonia Toxicity in Channel Catfish

Abstract: The twenty-four-hour median lethal concentrations (24-hour LC50) of total ammonia nitrogen (TA-N) to channel catfish (lctalurus punctatus) at pH 7, 8, and 9 (total hardness, 40 rag/liter; temperature, 21-25 C) were 263.6 -+ 11.3 (SE), 38.8 -+ 1.8, and 4.5 -+ 0.2 rag/liter, respectively. The 24-hour LC50 of un-ionized ammonia nitrogen (UIA-N) concentration at pH 8 was significantly higher (1.82 -+ 0.06 mg/liter) than at pH 7 or 9 (1.39 -+ 0.06 and 1.49 -+ 0.12 mg/liter). Enrichment of the water to 440 mg/liter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 15 publications
1
58
0
2
Order By: Relevance
“…It is known that ammonia produces a toxic effect in temperate fishes (Tomasso et al, 1980;Thurston et al, 1984;Peters et al, 1984). In tropical fish species, with potential for aquaculture, studies on lethal concentration of ammonia in fish have been initiated (Ostrensky & Brugger, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ammonia produces a toxic effect in temperate fishes (Tomasso et al, 1980;Thurston et al, 1984;Peters et al, 1984). In tropical fish species, with potential for aquaculture, studies on lethal concentration of ammonia in fish have been initiated (Ostrensky & Brugger, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia is a common pollutant of natural aquatic systems and constitutes the main nitrogenous waste compound (Tomasso et al, 1980). It is produced mainly in the fish liver (Goldstein et al, 1982), reaches the gills through the blood (Evans & More, 1988), and is excreted in the epithelium by a variety of means (Evans & Cameron, 1986) and then it is transferred to the water.…”
Section: Introductionmentioning
confidence: 99%
“…The main process of ammonia excretion in freshwater fish is by the passive transcellular diffusion of NH 3 down a concentration gradient (WRIGHT & WOOD, 1985;RANDALL & WRIGHT, 1987;CLAIBORNE & EVANS, 1988). Exposure to high waterborne NH 3 levels reduced plasma Na + in channel catfish (Ictalurus punctatus) (TOMASSO et al, 1980) and in rainbow trout (Oncorhynchus mykiss), and also increased Na + efflux in rainbow trout (TWITCHEN & EDDY, 1994). However, it did not change plasma ion levels in other experiments (WILSON & TAYLOR, 1992;VEDEL et al, 1998).…”
Section: Introductionmentioning
confidence: 86%
“…Exposures of teleosts to elevated environmental levels of ammonia have been found to result in degenerative gill and kidney damage (Burrows 1964, Smart 1976, Thurston et al 1978, reduced growth rates (Burrows 1964, Colt and Tchobanoglous 1978, Robinette 1976, reduced 02 carrying capacity of the hemoglobin (Sousa and Meade 1977), increased urine output (Lloyd and Orr 1969) and the release of corticosteroid hormones (Tomasso et al 1980). Additional research has indicated low dissolved oxygen enhances the toxicity of ammonia (Merkens and Downing 1957, Thurston et al 1981a, Lloyd 1961).…”
Section: Noncontaminant-related Toxicity Potentialmentioning
confidence: 99%